THE ROLE OF CITIZENS AND CIVIL SOCIETY ORGANIZATIONS IN THE DEVELOPMENT OF CITIZEN CULTURAL DIPLOMACY - Holoborodko, Oleh (Public Management and Policy, 2025)
The article is devoted to the current issues of the transformation of public cultural diplomacy in the modern global context, where citizens and civil society organizations are acquiring a decisive role in international cultural communications. The study analyzes the approaches of cultural diplomacy from traditional state-centric models to decentralized, networked forms of interaction. It is noted that the digital revolution has radically changed the mechanisms of international communication, democratizing the space of cultural exchange. The research methodology includes a comprehensive analysis of scientific sources, systematization of modern scientific approaches to the study of public cultural diplomacy with a special emphasis on the analysis of the role of non-state actors in the formation of international cultural narratives. The study revealed transformational processes in the field of cultural diplomacy. A comparative analysis of various non-state actors of cultural diplomacy is presented. The potential of citizens and civil society organizations as key actors of international communication is revealed. An analysis of the impact of popular digital platforms on cultural exchange is conducted. Recommendations are provided for improving diplomatic practices by creating adaptive institutional structures, developing digital skills, and implementing flexible mechanisms for assessing cultural impact. The scientific novelty of the study lies in the comprehensive analysis of the change in the paradigm of cultural diplomacy, where vertical communications are replaced by network forms of interaction. The study proves that modern cultural diplomacy is a complex area where citizens can act as carriers of intercultural dialogue. The transition from state-controlled communications to authentic, emotionally rich interpersonal interactions is important in modern conditions. The prospects for further research in this area should be considered the study of ethical aspects of global communication based on the activities of citizens and citizen society organizations.